Trap or opportunity—What role does geography play in the use of cash for childcare?. Issue 4 (7th January 2020) - Magnusson Turner, Lena; Östh, John
Abstract: After a heated debate, the Norwegian parliament voted for the introduction of Cash‐for‐Care (CFC) in 1997, a programme designed to give parents more opportunities to plan childcare. The pro‐CFC faction claimed that the reform would give parents more time with their children, whereas CFC opponents pointed to the increased risks of creating gender traps and discouraging women from returning to work. Earlier studies have suggested that the socio‐economic dimensions are important for understanding the use of CFC. However, the role of geography in the implementation of CFC has not been studied, though it is well‐known that the residential context is important to understand how parents choose to organize childcare. Our study is designed to examine the use of CFC in order to determine how much can be attributed to socio‐economic factors and how much can be attributed to geography. We focus on mothers who gave birth to their first child in 2009 and follow their life course through 2011. We use a unique and comprehensive longitudinal data set with annual economic, demographic, and geographical information that includes all mothers residing in Norway during the study period. We find that the use of CFC is strongly correlated with several socio‐economic variables and that there are also strong geographical factors, local and regional, affecting the choice to use CFC.